ANALISIS DAYA DUKUNG LAHAN DAN OPTIMASI PENDAPATAN USAHA TANI DI DAERAH TRANSMIGRASI KURO TIDUR, BENGKULU - Mulyono, Daru (Jurnal Rekayasa Lingkungan)
The objective of the research is to know the cultivation land scale of farmers according to kind of commodities in order to achieve the highest farm income subject to the low land carrying capacity condition. The research use Linear Programming Technique with subject to two main constraints, that are area of cultivation and availability of man power. The research was carried out in Wonoharjo Village, Unit VIII Kuro Tidur Transmigration area, Bengkulu. The method of sampling drawn was random sampling. Number of respondentswas 60 farmers who cultivate food crops as well as estate crops. The results of the research show that the highest farm income can be achieved to a high of Rp. 2.279.217,- a year or increase amount of Rp. 511.140,- a year or 28.9 % through intensive cultivation of wetland rice = 0.261 ha, upland rice = 0.188 ha, cassava = 0.120 ha, peanut = 0,101 ha, and coffee = 0.750 ha.Kaywords: Transmigration land income